Jointly owned forests and forest land consolidation – increasing the stand size in fragmented areas - Kolis, Karin (Nordic Journal of Surveying and Real Estate Research, 2015)
Private ownership has traditionally been seen as superior to joint ownership. The creation of new jointly owned forests is, nevertheless, seen as an integral part of Finnish forest land consolidation projects. Jointly owned forests are seen as a solution to the increasingly small forest properties, which lead to higher harvest and maintenance costs and lower incen-tives to manage the forest. In this study, a case study of the size of forest stands (compartments) before and a decade after the Pahkakoski land consolidation project is carried out. The stand sizes before and after land consolidation are compared both for areas that only underwent land consolidation, and for areas that were merged into a jointly owned forest. The results show that land consolidation increases the stand sizes, especially for younger stands. For jointly owned forests the increase is larger: for forest land the average stand size increased with between 1 and 1.8 hectares depending on the development class of the forest stand. The results show that land consolidation on its own can increase the stand size, leading to lower management costs, but that jointly owned forests increases this effect considerably. As such, creating jointly owned forests present benefits compared with pure land consolidation through economies of scale.